2018
DOI: 10.1007/s00299-018-2367-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-activated protein kinases MPK3 and MPK6 are required for stem cell maintenance in the Arabidopsis shoot apical meristem

Abstract: The CLAVATA peptide-receptor (CLV3p-CLV1) pathway modulates a homeodomain master regulator WUSCHEL (WUS) transcription factor in the shoot apical meristem (SAM) with poorly defined signaling mechanisms. Here, we report that mitogen-activated protein kinases (MAPKs, also known as MPKs in plants) act in an intracellular signaling cascade to play an important role in the maintenance of SAM development. Interestingly, the application of exogenous CLV3p triggers rapid signaling in the SAM via dynamic activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…It was reported that the CLV3 signaling can activate MPK6 to maintain SAM homeostasis [ 187 ]. A recent study showed that exogenous CLV3 can activate MPK3/6, and the mpk3/6 double mutant is insensitive to CLV3 treatment [ 10 ]. The transcription levels of WUS-target genes, such as ARABIDOPSIS RESPONSE REGULATOR 7/15 ( ARR7/15 ), GROWTH-REGULATING FACTOR 6 ( GRF6 ) and YABBY 3 ( YAB3 ), are decreased in mpk3/6 .…”
Section: Rlks and Mapk Cascades Function In Other Plant Developmenmentioning
confidence: 99%
See 3 more Smart Citations
“…It was reported that the CLV3 signaling can activate MPK6 to maintain SAM homeostasis [ 187 ]. A recent study showed that exogenous CLV3 can activate MPK3/6, and the mpk3/6 double mutant is insensitive to CLV3 treatment [ 10 ]. The transcription levels of WUS-target genes, such as ARABIDOPSIS RESPONSE REGULATOR 7/15 ( ARR7/15 ), GROWTH-REGULATING FACTOR 6 ( GRF6 ) and YABBY 3 ( YAB3 ), are decreased in mpk3/6 .…”
Section: Rlks and Mapk Cascades Function In Other Plant Developmenmentioning
confidence: 99%
“…However, the SAM is still normal in most mpk3/6 mutants treated with exogenous CLV3. Moreover, the size of the SAM in mpk3/6 is larger than the wild type [ 10 ]. All these findings suggest that the CLV3-CLV1 signaling pathway regulates stem cell homeostasis in the SAM possibly via activating a MAPK cascade including MPK3/6.…”
Section: Rlks and Mapk Cascades Function In Other Plant Developmenmentioning
confidence: 99%
See 2 more Smart Citations
“…Mitogen-activated protein kinase (MAPK) cascades, which display a classical mode of intracellular signal transduction in RLK pathways (reviewed in (He et al, 2018)), have been proposed to mediate downstream CLE signaling (Betsuyaku et al, 2011;Lee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%